Interação simbiótica de bactérias e doses de nitrogênio no cultivo da soja - Cunha , Letícia do Socorro (2020)
The objective of this work was to evaluate inoculation, co-inoculation with B. japonicum and A. brasilense bacteria in combination with application of N doses on the agronomic characteristics of soybean in two experiments (greenhouse and field) in the 2018 harvest / 2019. The experimental design used in both was the randomized block (DBC), in a 4x4 factorial scheme with four replications, four types of inoculation (without inoculation, inoculation of the bacterium B. japonicum, inoculation of the bacterium A. brasilense and inoculation of the bacteria B japonicum and A. brasilense in combination) and four percentage doses of N (0, 2, 4 and 8 %). As for the evaluations, for both experiments, they were carried out at the beginning of flowering (stage R1) to evaluate the components of nodulation and N content and accumulation in the plant; and at full maturation (stage R9) to evaluate the agronomic traits of the crop. The use of inoculation in association with the application of nitrogen doses did not influence the variables of plant height, number of pods per plant, number of grains per pod and soybean yield for both experiments. The number of nodules and the root dry mass were higher at the dose of 8 % N, with an average of 317 nodules per plant and 23.42 g plant-1, respectively, when inoculated with A. brasilense. The nodulation efficiency increased when the dose of 2 % N was used, with a value of 354 g kg-1, using the bacterium A. brasilense. The accumulation of N in the aerial part, obtained a maximum value in the dose of 8 %, which in this case corresponded to 142 g of N kg-1 with co-inoculation, presenting different response capacity for the characters dry root mass and number of grains per protected crop. In field conditions, the number of nodules was higher in the dose of 2 % with averages of 46 nodules per plant when inoculated with B. japonicum, and in the variables of dry masses of nodules, roots and shoots when inoculated with A. brasilense at the 8% dose, they obtained higher averages with 486.94 mg plant-1, 11.91 g plant-1, 95.5 g plant-1, respectively. The nodulation efficiency increased linearly when the dose of 8 % N was used, with a value of 72.32 g kg-1. For the characters number of nodules and nodulation efficiency, there was a significant increase when the dose of 2 % N was used, associated with the practice of nitrogen fertilization and 8 %, the dry mass of nodules, root, aerial part and nodulation efficiency. , obtained more satisfactory results than the other doses.